1997
DOI: 10.1007/s004120050219
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin protein HP1 Hsβ (p25β) and its localization with centromeres in mitosis

Abstract: Some autoimmune sera containing anticentromere autoantibodies also recognize a doublet of Mr 23 000 (p23) and 25 000 (p25) in addition to CENP (centromere protein)-A (Mr 19 000), -B (Mr 80 000), and -C (Mr 140 000). A p25 antigen (HP1(Hsalpha)) has been shown to be a human homolog of Drosophila HP1 (heterochromatin protein 1). We have isolated a cDNA clone encoding another form of p25 (HP1(Hsbeta ) or p25beta) from a lambdaZap HepG2 library using human autoimmune serum. The deduced amino acid sequence of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…1D). The 5 genes include 3 with well-established roles in FASinduced apoptosis (11,(13)(14)(15) (FAS, FADD, and CASP8) and 2 previously undescribed genes-ARID1A, a SWI/SNF chromatin remodeling complex component (16,17), and CBX1, a chromatin silencing protein (18). For all 5 genes, the effective shRNAs also inhibited both FAS-induced CASPASE 8 cleavage and FASinduced mitochondrial leakage (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…1D). The 5 genes include 3 with well-established roles in FASinduced apoptosis (11,(13)(14)(15) (FAS, FADD, and CASP8) and 2 previously undescribed genes-ARID1A, a SWI/SNF chromatin remodeling complex component (16,17), and CBX1, a chromatin silencing protein (18). For all 5 genes, the effective shRNAs also inhibited both FAS-induced CASPASE 8 cleavage and FASinduced mitochondrial leakage (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Different studies using different cell lines and experimental approaches have shown partial to complete loss of HP1 from mitotic chromatin. [43][44][45][46][47][48] The consensus seems that at this stage of the cell cycle, all of HP1b and HP1g, as well as the majority of HP1a, dissociate from chromatin. Only a fraction of HP1a remains localized at the centromeres.…”
Section: Mitotic Release Of Hp1 From Chromatinmentioning
confidence: 99%
“…46 If phosphorylation of H3S10 is indeed sufficient to abolish interaction of the chromo domain of all HP1 isoforms with H3K9me3, globally releasing them from mitotic chromatin, then separate mechanisms must exist to anchor HP1a at the centromere. Interestingly, HP1a itself is subject to extensive post-translational modifications, 44 which appear to regulate its association with other chromatin components. 61 In vitro, the CPC complex phosphorylates residues in the HP1a hinge region (our unpublished observations), which might mediate the retention of this isoform at the centromere, possibly via interaction with the CPC and/or phosphorylated histone H3.…”
Section: Mitotic Release Of Hp1 From Chromatinmentioning
confidence: 99%
“…HP1β has therefore been implicated in a wide range of possible functions including transcriptional repression (Ryan et al, 1999), transgene silencing (Festenstein et al, 1999), chromosome segregation (Wang et al, 2000) and nuclear envelope reassembly (Kourmouli et al, 2000). HP1β is predominantly found in pericentromeric constitutive heterochromatin in mitotic (Wregett et al, 1994;Furuta et al, 1997) and meiotic cells (Motzkus et al, 1999) and it is concentrated in the XY-body of late-pachytene and diplotene spermatocytes (Motzkus et al, 1999;Turner et al, 2001). HP1β is a dose-dependent modifier of a variegating position effect (Festenstein et al, 1999).…”
Section: Introductionmentioning
confidence: 99%